Molecular regulation of kidney development - Chai, Ok-Hee; Song, Chang-Ho; Park, Sung-Kwang; Kim, Won; Cho, Eui-Sic (Anatomy & cell biology, 2013)
Genetically engineered mice have provided much information about gene function in the field of developmental biology. Recently, conditional gene targeting using the Cre/loxP system has been developed to control the cell type and timing of the target gene expression. The increase in number of kidney-specific Cre mice allows for the analysis of phenotypes that cannot be addressed by conventional gene targeting. The mammalian kidney is a vital organ that plays a critical homeostatic role in the regulation of body fluid composition and excretion of waste products. The interactions between epithelial and mesenchymal cells are very critical events in the field of developmental biology, especially renal development. Kidney development is a complex process, requiring inductive interactions between epithelial and mesenchymal cells that eventually lead to the growth and differentiation of multiple highly specialized stromal, vascular, and epithelial cell types. Through the use of genetically engineered mouse models, the molecular bases for many of the events in the developing kidney have been identified. Defective morphogenesis may result in clinical phenotypes that range from complete renal agenesis to diseases such as hypertension that exist in the setting of grossly normal kidneys. In this review, we focus on the growth and transcription factors that define kidney progenitor cell populations, initiate ureteric bud branching, induce nephron formation within the metanephric mesenchyme, and differentiate stromal and vascular progenitors in the metanephric mesenchyme.